Józef Wieniawski - Ferenc Liszt. Concert etude examined from the perspective of the genre - Tatarska, Janina (Interdisciplinary Studies in Musicology, 2018)
The cycle 24 Etudes in All Major and Minor Keys op. 44 by Józef Wieniawski (1837-1912) demonstrates the essential unity of the virtuoso and the composer in a dynamic process of transforming the genre. This played an important part in providing innovative solutions not only in relation to piano-playing, but also in its significant influence on the development of texture, diversification of the instrumental sound and the expansion of means of musical expression in nineteenth-century piano music. Wieniawski, following Transcendental etudes or Concert etudes by Liszt, whose pupil he was in Weimar, blurs the boundaries between improvisation and composition; he draws attention to the unique nature of interpretation, its singularity and the specificity of the moment in time when the work is performed. Continuing the tradition of the grand cyclic form as a special kind of universum, he implements the concept of diversity in unity. The 24 characteristic miniatures reveal contextual links, intra-musical relationships, and the quest for individual solutions. This problematic concerns issues such as symbolic references, which lead one to an extensive catalogue of expressive qualities.